2003
DOI: 10.1159/000068069
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Interleukin-6 in Cervical Secretions and Assessment of the Uterine Cervix by Transvaginal Ultrasonography Predict Preterm Premature Rupture of the Membranes

Abstract: Objective: The objective of this study was to investigate the predictive factors of premature rupture of the membranes (preterm PROM). Methods: The study was undertaken with cervical secretions collected from 72 consenting singleton pregnant women between 20 and 33 weeks of gestation. The levels of interleukin (IL) 1α, IL-1β, IL-6, IL-8, matrix metalloproteinase (MMP) 1, MMP-2, MMP-9, tissue inhibitors of matrix metalloproteinase (TIMP) 1, TIMP-2, granulocyte elastase, and fetal fibronectin in cervical diluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The heterogeneity of spontaneous PTB and the various clinical presentations (asymptomatic or symptomatic) provide significant challenges for the identification of a single biochemical marker to reliably predict all PTB (Menon et al, 2011 ; Bhat et al, 2013 ). The concept of utilizing multiple biochemical markers to improve labor prediction has been reported by our team (Heng et al, 2010a , 2014b ; Liong et al, 2015 ) and others (Rizzo et al, 1998 ; Goldenberg et al, 2001 ; Kishida et al, 2003 ; Grenache et al, 2004 ; Taylor et al, 2013 ). Other variations of using a diagnostic panel to predict PTB include incorporating peripheral blood results, gene expression profiles (Heng et al, 2014a ) as well as combining demographic, physical and behavioral parameters (e.g., cervical length or illicit drug use) (Hincz et al, 2002 ; Schmitz et al, 2006 ; Dutta and Norman, 2010 ; Bolt et al, 2011 ; Dekker et al, 2012 ; Fox et al, 2012 ; DeFranco et al, 2013 ).…”
Section: Multiple Biomarker Prediction Of Human Parturition and Its Cmentioning
confidence: 86%
“…The heterogeneity of spontaneous PTB and the various clinical presentations (asymptomatic or symptomatic) provide significant challenges for the identification of a single biochemical marker to reliably predict all PTB (Menon et al, 2011 ; Bhat et al, 2013 ). The concept of utilizing multiple biochemical markers to improve labor prediction has been reported by our team (Heng et al, 2010a , 2014b ; Liong et al, 2015 ) and others (Rizzo et al, 1998 ; Goldenberg et al, 2001 ; Kishida et al, 2003 ; Grenache et al, 2004 ; Taylor et al, 2013 ). Other variations of using a diagnostic panel to predict PTB include incorporating peripheral blood results, gene expression profiles (Heng et al, 2014a ) as well as combining demographic, physical and behavioral parameters (e.g., cervical length or illicit drug use) (Hincz et al, 2002 ; Schmitz et al, 2006 ; Dutta and Norman, 2010 ; Bolt et al, 2011 ; Dekker et al, 2012 ; Fox et al, 2012 ; DeFranco et al, 2013 ).…”
Section: Multiple Biomarker Prediction Of Human Parturition and Its Cmentioning
confidence: 86%
“…In a study performed by Rizzo et al [32] in patients with preterm labor, the IL-6 levels in cervical secretions were significantly correlated with the intra-amniotic levels of IL-6, and Kishida et al [33] reported that increased levels of IL-6 in cervical secretions and assessment of the uterine cervix by transvaginal ultrasonography predicted PPROM. These reports indicate the importance of IL-6 in PPROM and are supported by the findings of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies on low‐risk women have shown increased predictive performance by the following combinations of biomarkers: CL with fFN (51,52), CL with cytokines (53), cytokines in combination with other biochemical markers (15,54), CRH with alpha‐fetoprotein (AFP) (40), vaginal pH with fFN (55), BV with fFN (56), and BV in combination with genetic susceptibility (57). The most promising study has been the Preterm Prediction Study, which evaluated the predictive abilities of five biomarkers (AFP, alkaline phosphatase, G‐CSF, fFN, and CL) in a case‐control study with 50 preterm deliveries (<32 weeks) and 127 matched term controls (58).…”
Section: Multiple Markersmentioning
confidence: 99%